RELATIONSHIP BETWEEN BLOOD PRESSURE AND BLOOD GLUCOSE ON VASCULAR BLOOD FUNCTION AND AEROBIC WORKING CAPACITY IN FEMALE NURSE'S SHIFT WORK - Ike Rahmawaty Alie; Yuke Andriane; Rizki Perdana; Doni Septiadi Rosady; Ieva B Akbar (Journal of Health and Dental Sciences, 2022)
Shift work is a rotating work time outside regular working hours, either rotating with the shift work method. Shift work can cause changes in metabolism, immunological status, and oxidative status that cause inflammation due to changes in circadian rhythm. Nurses, primarily female, in provide 24-hour services also have to do shift work. This study aimed to see the relationship between blood pressure and blood glucose to vascular function and aerobic capacity in female nurses working in hospitals. The research method was descriptive-analytic to know the relationship between blood pressure and glucose to blood vessel function as measured by cGMP and aerobic capacity. Through VO2max, the research sample was selected purposively with inclusion criteria of having worked as female nurses who had worked for at least six months and were aged 20-40 years. The results show that the fasting blood glucose value had more influence on the cGMP value than the MABP value (r= 0.204 vs. 0.034), although the relationship was weak and very weak. The correlation analysis between fasting Blood Glucose and VO2max and Blood Pressure with VO2max shows blood pressure is more significant than fasting Blood Glucose on VO2max (0.105 vs. 0.083) even though the correlation between the two is very weak. It may be because many other factors can influence blood vascular function and aerobic functional capacity. DOI : 10.54052/jhds.v2n1.p1-14